(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the development of personal qualities in children through a collaborative methodology involving both parents and educators. The formation of such qualities—responsibility, empathy, self-confidence, discipline, and social awareness—is a fundamental task of early childhood education. While schools provide structured environments for learning, the family remains the child’s first and most influential institution of socialization.